Estimation of water consumption in multifamily residential buildings - Souza, Camilla de; Kalbusch, Andreza (Acta Scientiarum. Technology, 2017)
This article shows an estimation of water expenditure in multifamily residential buildings in the city of Joinville, located in south Brazil. The proposed method includes an investigation of the water expenditure and an evaluation of the particularities of each building. The investigation was accomplished in thirty buildings and the collected data allowed a classification of the buildings and a measurement of the water consumption rate. The water consumption in buildings with individualized and collective water measurement systems was analyzed. Furthermore, a comparative study was done between the water consumption in buildings that have at least one pool and buildings without any pools. Some buildings in the sample have an alternative water supply system; however there is no measurement of the water consumption in none of the cases analyzed in this study. The per capita consumption was 224 liters per person per day. The buildings with individualized water measurement had smaller consumption per capita than the buildings with collective measurement, showing a reduction of about 34%. The buildings with pools had consumption per capita nearly 48% more than the per capita consumption in buildings without pools. Â